Urethanes and polyurethanes from suberin 2: synthesis and characterization (INDUSTRIAL CROPS AND PRODUCTS, 1999)
Polyurethanes based on suberin from cork of Quercus suber L. and conventional isocyanate monomers were prepared and fully characterized in terms of both structure (FTIR and H-1 NMR spectroscopy) and thermal properties (differential scanning calorimetry and thermogravimetric analysis). Two fractions were systematically isolated, namely (i) methylene-chloride soluble products, which corresponded to linear and branched macromolecules and (ii) methylene-chloride insoluble products, representing the crosslinked material. The structures of these polymers were regular and no appreciable side reactions were detected. DSC analyses provided information about the glass transition temperature of both fractions and this parameter was correlated with the stiffness of the isocyanate used. The TGA of these polyurethanes showed that they started to degrade at about 175 degrees C and that the residue at 400 degrees C was around 50%. The highest amounts of insoluble fractions, as well as the highest T-g,s, were reached when an initial \{[\}NCO]/\{[\}OH] of unity was used. (C) 1999 Elsevier Science B.V. All rights reserved.

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.

Suberin-based polyurethanes: Synthesis, characterization and kinetics of their formation (BIOMASS FOR ENERGY AND INDUSTRY, 1998)
The synthesis and characterization of novel family of polyurethanes prepared by the polycondensation of suberin from Quercus suber L. with aliphatic and aromatic isocyanates are reported. A preliminary kinetic study, conducted with the aim of establishing the reactivity of suberin with different mono-, di- and polyisocyanates, showed that the kinetics of these condensations followed the classical second-order behaviour up to conversion of about 90%. The reactivity of different isocyanates followed patterns that could be readily rationalized in terms of steric hindrance and electronic factors, associated with each specific structure. The investigation was then extended to the synthesis of the new polymers which were characterized by FTIR and NMR spectroscopy and DSC. These suberin-based polyurethanes were a mixture of linear, branched and crosslinked structures. The proportion of the latter (insoluble fraction) being the highest for thr syntheses carried out in stoichiometric conditions, viz. \{[\}NCO](o) = \{[\}OH](o). The Tg of these materials depended of the diisocyanates used and correlated with their structural stiffness.